Penerapan Pengasap Ikan Laut Bahan Bakar Tempurung Kelapa - Komar, Nur (Fakultas Teknologi Pertanian Universitas Brawijaya, 2001)
Hopefully the adoption of the fish curing technology is able to open a new and alternative work for people, especially whose daily job is on this field. Pioneering, demonstration and training in a small scale certainly can not reach yet the social stratum widely. It can be so, because of the limitedness. The purpose of this program is multiple furnace (tungku ganda) making and planning process partitioned by air in order that the coconut shell fuel can be used for curing sea fish economically, 2) Determination of water steam quick, efficiency of heat, calculation the expense to determine the sale price, 3) Evaluating the success level of cured sea fish product either technically, economically or socially. The advantages of this program are in the field such as : `1) Academic can broaden the science about the theoretically of heat energy balance, then being applied to society, 2) The advantages for the society by curing coconut shell-burned fist hopefully it can reduce the social imbalance developing in the fisher society that need properly used technology, 3) The advantages for common development for the sake of increasing fisher village area, especially overcoming of the underdeveloped village and realization of the program back to village. In the paradigm of realization that involves problem solving, objective, and the developed method, surely, there are many weaknesses that should be improved in the future for the sake of perfection. The sea fish curing sawdust fuel has been held during November until December 1999 involved planning and making of coconut shell burned sea fish can be well operated. Rate of evaporation can be reached during curing is 3 % (three percent) per hour, the efficiency of total heat is 78.5 % and the profit in Rp 500 per kilogram of the cured fish. And the grade success of sea curing technically, economically and socially can be continued positively with the existing prospect. Keywords: sea fish, curing technology, sawdust fuel